THE IMPACT OF TECHNOLOGY AND SOCIAL MEDIA ON THE INCREASE IN DIVORCE CASES - Nadriana, lenny; Idham; Maulidiana, Lina (Progressive Law Review, 2024)
This study examines the impact of social media on divorce rates in Bandar Lampung City. The phenomenon of social media and information technology has influenced the way people communicate, make friends, and establish romantic relationships. The problem in this study is why divorce can be caused by media use. This study aims to identify how social media plays a role in increasing divorce rates.This study uses a qualitative research method with a library study and case study approach. The study's results indicate that the development of social media impacts divorce rates and acts as a risk factor in marriage. It can trigger jealousy and distrust and cause disputes that lead to divorce. Social media has also become a means of online shopping and then online gambling, affecting economic factors that ultimately cause chaos and divorce.